E-cadherin基因启动子区甲基化与肺癌易感性的meta分析研究 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: As a member of the cadherin superfamily, E-cadherin plays a critical role in the maintenance of cell polarity and integrity. And E-cadherin was reported to be down-regulated and closely related to tumor initiation, invasion and metastasis. There have been a number of studies investigating the methylation of E-cadherin promoter in relation to various cancers. However, the association between E-cadherin promoter methylation and lung cancer risk is controversial. The aim of the present study is to evaluate the association of E-cadherin promoter methylation with risk of lung cancer by conducting a systematic meta-analysis. METHODS: Relevant studies were identified by searches of PubMed/MedLine and EMBASE databases before March 2013. Combined odds ratio (OR) and 95% confidence interval (CI) were used to assess the strength of the association between E-cadherin promoter methylation and lung cancer risk. RESULTS: A total of 1, 288 samples from 13 independent studies were included in the meta-analysis. Overall, a significant association was observed between E-cadherin promoter methylation and lung cancer risk (OR=4.04, 95%CI: 2.00-8.13, P < 0.001). Subgroup analyses by ethnic revealed that lung cancer risk was increased for individuals carrying the methylated E-cadherin in Asian and Caucasian populations (OR=3.28, 95%CI: 1.20-8.92; OR=5.72, 95%CI: 2.40-13.62). CONCLUSION: The present meta-analysis indicates that the methylation of E-cadherin promoter is associated with risk of lung cancer.